In‐situ measurement of grain size characteristics within the aeolian saltation layer on a coastal beach. Issue 9 (24th April 2022) - Cohn, Nicholas; Dickhudt, Patrick; Marshall, John
Abstract: Sediment grain size has a first‐order control on aeolian transport rates due to threshold effects. However, there remain limited in‐situ approaches to measuring properties of sediment size within the saltation layer in field environments. Here, a demonstration of in‐line holography for generating quasi‐3D images of saltating particles near the bed during an aeolian transport event is presented. A vertical fining of sediment grain size in the 50 mm above the bed is found for time‐averaged results. At shorter timescales this fining trend is not unconditionally true as the instantaneous positions of individual saltating particles is dependent on their trajectories. Whereas both the number of particles and sediment concentrations increase with rising wind speeds, the measurements suggest that median grain size coarsened with time despite reducing wind speeds—likely due to winnowing of fine sands from the surface bed layer. Trends found using the holographic sensor are confirmed with traditional measurement techniques, with deviations between these various measurement approaches analyzed and discussed. The data here collectively demonstrate the ability of off‐the‐shelf in‐line holographic technology to provide new insights into detailed particle‐scale aeolian sediment transport dynamics. Abstract : Measurements collected using an in‐line holographic camera system during windy conditions on a coastal beach showed a general fining of the particle size distribution upwards from the bed within the aeolian saltation layer. The median grain size of saltating grains also coarsened with time, despite a reduction in wind speed, presumably due to changing sediment supply of the bed. These trends derived from the holographic camera are confirmed against traditional measurement techniques in this study.